Analysis of Student Needs for The Development of Project-Based Learning Digital Modules to Improve Understanding of Concepts in Aviation English Courses - Masito, Fitri; Danim, Sudarwan; Badeni, Badeni; Komalasari, Yeti; Maryansyah, Yupika (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The research aims to analyze student needs for developing project-based learning digital modules to improve understanding of concepts in the Aviation English course. A total of 77 cadets who took the Aviation English course at the Politeknik Penerbangan Palembang were involved in the research conducted from May to June 2023. The research instrument used is a closed questionnaire sheet that has four answer choices. Analysis of cadets' needs to develop project-based digital modules was carried out using descriptive statistical analysis. This is done by processing percentage data from filling out cadet questionnaires. The percentage is obtained based on the calculation of the modified Likert Scale. The results showed that as many as 77 respondents or 100% of respondents strongly agreed to the development of project-based learning digital modules to improve understanding of concepts in the Aviation English course